The Moderation of Al-Qaradhawi's Fatwas and Their Actualization in the Contemporary Context - Muchtar, Nurkhalis (MAQASIDI: Jurnal Syariah dan Hukum, 2024)
The process of providing answers to problems that arise or questions that arise is called a fatwa. The need for fatwas was felt from the beginning of the development of Islam. In Islam, fatwas have a high position so not everyone can give fatwas. Fatwas that come from non-experts will cause fatal mistakes in society. Islamic scholars have poured their thoughts on fatwas in various scientific works. However, there has been no work that examines the moderation of fatwas in the current context. On the other hand, there is also a paradigm that is wrong in making fatwas, some are too rigid and some are too flexible in making fatwas. Al-Qaradhawi as a leading jurist offers a breakthrough in fatwa, especially a new paradigm in fatwa. This study uses a qualitative descriptive research method on the findings of library data, with the approach of library research and content analysis, it is concluded that Al-Qaradhawi initiated the idea of moderation in the fatwa. This research also reveals that the moderate fatwa of Al-Qaradhawi is considered relevant to be applied in the current era. This research is expected to be one of the efforts to initiate the moderation of fatwas and their actualization in the current context so that there can be a fatwa that can realize stability, justice, and benefits in the life of human beings as a nation and homeland.